Training Concerns of Micro-influencers on Advertising and Marketing - Fernández-Gómez, Erika; Feijoo, Beatriz; Morante Bonet, Miriam (Journal of Advertising Education, 2024)
Influencers have emerged as influential figures un bridging the gap between brands and consumers, establishing this practice as a viable profession in advertising. Among the diverse spectrum of influencers, micro-influencers, characterized by their follower count of less than 100,000, excel in fostering engagement due to their perceived authenticity and credibility. This study surveyed 290 micro-influencers regarding their educational needs and aspirations. The findings reveal that, despite possessing university degrees, micro-influencers often lack specialized training in digital content creation. Many express a strong desire to receive formal education at the university level to enhance their professionalism, with degrees in marketing or advertising being deemed particularly relevant. However, they encounter significant obstacles, primarily related to financial constraints and time availability. Consequently, universities face the imperative challenge of contributing to the professionalization of micro-influencers, a role that has traditionally been assumed by the industry.
Keywords: advertising; marketing; social influence; teaching and training; career; professional profile; social influence; professional profile